Influence of product quality, brand image and price on consumer satisfaction of Amanda brownies in the city of Probolinggo - Rahajeng, Yekti (Central Research Institute for Agriculture (CeRIA), 2024)
This study aims to determine the effect of product quality, brand image and price partially and simultaneously on consumer satisfaction of AmandaBrownies in Probolinggo City. The population of this study are consumers who have purchased Amanda Brownies in Probolinggo City. The data collection technique used a query. In addition, this study used a sample of 104 people with a sampling method, namely incidental sampling. This type of research is causal associative. Data processing in this study used SPSS version 23. Data analysis methods are validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination and hypothesis testing. The results of this study indicate that product quality (X1) has a positive and significant effect on customer satisfaction (Y) with at test value of 4.810 and is at a significance of 0.000 and the regression test results are 0.383, brand image (X2) has a positive and significant effect on customer satisfaction (Y) with at test value of 1.948 and is at a significance of 0.004 and the regression test results are 0.238, and price (X3) has a significant positive effect on customer satisfaction (Y) with at test value of 4.310 and is at a significance of 0.000 and the regression test results are 0.449. The results of statistical analysis obtained an F count value of 27.883 > 2.694 and a significance of 0.000 < 0.05. So that there is a joint influence of the variables of product quality (X1), brand image (X2) and price (X3) on customer satisfaction of Amanda Brownies in Probolinggo City.